PERLINDUNGAN HUKUM PEKERJA KESEHATAN: ANALISIS EKONOMI TERHADAP KESEJAHTERAAN DAN KINERJA - Vinanda Langgeng Kencana; Rina Arum Prastyanti; Sari Yudianti Suwardji (Universitas Duta Bangsa Surakarta, 2025)
This article discusses legal protection for healthcare workers as a fundamental aspect in ensuring the continuity and effectiveness of the healthcare system in Indonesia. This study aims to analyze the forms of legal protection provided to medical personnel and their impact on their welfare and performance using a legal economic analysis approach. The results of the study show that although there are a number of regulations governing the rights and obligations of healthcare workers, their implementation in the field is still not optimal. Legal uncertainty, unequal protection, and a lack of legal assistance have a direct impact on the psychological well-being and job stability of medical personnel. Additionally, weak legal protection also negatively affects productivity, loyalty, and the efficiency of healthcare services. Therefore, legal protection should be viewed as a strategic investment capable of enhancing the performance of medical personnel and strengthening the national healthcare system as a whole. This study recommends the need for a reformulation of legal policies and the strengthening of protective mechanisms that are more concrete and oriented toward justice and efficiency.